2023
DOI: 10.3389/fendo.2023.1034266
|View full text |Cite
|
Sign up to set email alerts
|

Effects of galactooligosaccharides on maternal gut microbiota, glucose metabolism, lipid metabolism and inflammation in pregnancy: A randomized controlled pilot study

Abstract: BackgroundGut microbiota of pregnant women change with the gestational week. On the one hand, they participate in the metabolic adaptation of pregnant women. On the other hand, the abnormal composition of gut microbiota of pregnant women is more likely to suffer from gestational diabetes mellitus (GDM). Therefore, gut microbiota targeted treatment through dietary supplements is particularly important for prevention or treatment. Prebiotic supplements containing galactooligosaccharides (GOS) may be an intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The study found that administering probiotic supplementation improved pregnancy outcomes and various glucose and lipid metabolism indicators, including insulin resistance. Wan performed an intervention involving 52 pregnant women, where galactooligosaccharides (GOS) were administered as a prebiotic supplement (Wan et al 2023 ). However, no significant benefits on glucose and lipid metabolism were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that administering probiotic supplementation improved pregnancy outcomes and various glucose and lipid metabolism indicators, including insulin resistance. Wan performed an intervention involving 52 pregnant women, where galactooligosaccharides (GOS) were administered as a prebiotic supplement (Wan et al 2023 ). However, no significant benefits on glucose and lipid metabolism were observed.…”
Section: Discussionmentioning
confidence: 99%
“…and hyperinsulinemia in pregnant women with obesity or overweight [95]. Furthermore, in healthy women, supplementation with galactooligosaccharides during pregnancy increased the abundance of Paraprevotella and Dorea, whereas the abundance of Lachnospiraceae was decreased, although these changes did not affect the incidence of GDM [82]. While these studies show that dietary fibre affects microbiota composition and metabolic responses in pregnancy, a limited number of studies have investigated the effect of dietary fibre supplementation on microbiota composition and diversity in women with GDM.…”
Section: Fibrementioning
confidence: 99%
“…Furthermore, high dietary fibre intake has been associated with a reduced incidence of GDM, while low dietary intake has been associated with an increased risk of GDM [78][79][80][81]. While a study in healthy pregnant women failed to show beneficial effects of a galactooligosaccharide intervention on glucose and lipid metabolism [82], the modification of maternal diets to increase fibre content has been shown to improve glycemic control in women with GDM [83]. Discrepancies between the studies could be attributed to the different types and amount of fibre supplementation and may indicate that fibre supplementation as a therapeutic tool may need to be considered in the context of levels of baseline fibre intake [84].…”
Section: Fibrementioning
confidence: 99%
“…Only a few (but well-designed) studies evaluated the effect of prebiotics, mainly galactooligosaccharides (GOS) and long-chain fructooligosaccharides (lcFOS), on infant gut microbiota [51,63]. A placebo-controlled RCT of 52 pregnant women explored the possible effects of GOS supplementation on maternal intestinal microbiota, inflammation and energy pathway [64]. Individuals receiving GOS had an increased level of Paraprevotella and Dorea but less Lachnospiraceae compared to those in the placebo group [64].…”
Section: Probiotics and Prebiotics During Pregnancy And Lactationmentioning
confidence: 99%
“…A placebo-controlled RCT of 52 pregnant women explored the possible effects of GOS supplementation on maternal intestinal microbiota, inflammation and energy pathway [64]. Individuals receiving GOS had an increased level of Paraprevotella and Dorea but less Lachnospiraceae compared to those in the placebo group [64]. Another RCT found a positive correlation between maternal FOS intake and bifidobacterial count in the mothers but not in the neonates [65].…”
Section: Probiotics and Prebiotics During Pregnancy And Lactationmentioning
confidence: 99%